Bitcoin Price Prediction Using Deep Learning - B. Revathi; Meena. M; Monica. S; S. V. Nayana Kumari (International Journal on Human-Computing Studies, 2022)
Bitcoin is an online currency developed in 2009. Bitcoin is a visual and cloud-based record that any individual authority can control. The cost of bitcoins has increased dramatically, and it is difficult to predict future costs with each Bitcoin. This project uses an in-depth study model to predict Bitcoin value to analyze the digital currency market. The proposed system uses the LSTM algorithm to predict the price of bitcoin in advance. This program can provide many of the key features needed to predict the level of bitcoin in the system. This model helps the user to decide to invest in Bitcoin.